Different interventions for post-ischaemic stroke depression in different time periods: a single-blind randomized controlled trial with stratification by time after stroke. (January 2017) - Gao, Jie; Lin, Meiqing; Zhao, Jiuhan; Bi, Siwei; Ni, Ziyan; Shang, Xiuli
Objective: To determine the appropriate treatments for post-ischaemic stroke depression at different times after stroke. Design: A single-blind, randomized, controlled trial that compared three intervention groups, with subgroups stratified by time after stroke. Setting: Outpatient clinic. Subjects: Eligible patients were recruited at discharge ( n = 73) and three ( n = 67), six ( n = 65), and nine months ( n = 69) after discharge, and patients completed mood questionnaires. Interventions: Patients were randomly distributed into three groups: Group A received placebos and participated in general discussions; Group B, received citalopram and participated in general discussions; and Group C, received placebos and underwent cognitive behavioural therapy. All three groups participated in rehabilitation during three months of follow-up. Main measures: Outcome was assessed three months after baseline using the 17-item Hamilton Depression Scale (HAMD17 ) and the Bech–Rafaelsen Melancholia Scale (MES). During treatment, the Udvalg for Kliniske Undersogelser side-effect scale was also administered. Results: When stratification was not considered, the scores of Group B on the Melancholia Scale were lower than those of Group A ( P = 0.02); when the four time-based subgroups were analysed, significant differences were observed between Groups A and B (PMES = 0.02, PHAMD17 = 0.02) in the group recruited six months after discharge and between Groups A and C (PMES = 0.01) in the last time period nine months after discharge. Conclusions: The effects of citalopram or cognitive behavioural therapy is similar to the effect of rehabilitation alone for early-onset post-ischaemic depression; rehabilitation and citalopram for delayed-onset post-ischaemic depression; and rehabilitation and cognitive behavioural therapy for late-onset post-ischaemic depression are more effective than rehabilitation alone.